2009
DOI: 10.1017/s000768050000091x
|View full text |Cite
|
Sign up to set email alerts
|

Ford's Investment in Colonial Malaya, 1926–1957

Abstract: The corporate history of Ford in Malaya from 1926 to 1957 reveals Ford Canada's global strategy to tap new British colonial markets. A combination of factors motivated Ford Canada to set up a subsidiary in Malaya, whose subsequent domestic sales and marketing success depended on maintaining mutually beneficial relations with the local merchant firms and Chinese entrepreneurs. After it was directed by the parent company to restructure its operations, Ford Canada imposed tight control on its own local operations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Still, London remained one of the most important financial centres of the world throughout the period under examination in this article (Michie 2006;Cassis 2010). Furthermore, most of the capital invested in Malaya during the period under study originated in Britain (Latham 1978, 55-56;van Helten and Jones 1989, 163-64;Rasiah 1995, 50;Lindblad 1997, 64;Drabble 2000, 54;Twomey 2000, 139), while only a minor share came from other parts of the world, including, for example, Australia, USA, China and Japan (Leng 1974;Birch 1976;Lindblad 1998, 22;64;Hillman 2005;Yacob 2009;Latham 1978, 55-56;Jelenkovic et al 2016, 163-64;Rasiah 1995, 50;Drabble 2000, 54;Twomey 2000, 139). Previous research has shown that the degree of international integration of financial markets for ventures that were operating internationally was high already in the nineteenth century (Campbell and Rogers 2017).…”
Section: Methods and Datamentioning
confidence: 99%
“…Still, London remained one of the most important financial centres of the world throughout the period under examination in this article (Michie 2006;Cassis 2010). Furthermore, most of the capital invested in Malaya during the period under study originated in Britain (Latham 1978, 55-56;van Helten and Jones 1989, 163-64;Rasiah 1995, 50;Lindblad 1997, 64;Drabble 2000, 54;Twomey 2000, 139), while only a minor share came from other parts of the world, including, for example, Australia, USA, China and Japan (Leng 1974;Birch 1976;Lindblad 1998, 22;64;Hillman 2005;Yacob 2009;Latham 1978, 55-56;Jelenkovic et al 2016, 163-64;Rasiah 1995, 50;Drabble 2000, 54;Twomey 2000, 139). Previous research has shown that the degree of international integration of financial markets for ventures that were operating internationally was high already in the nineteenth century (Campbell and Rogers 2017).…”
Section: Methods and Datamentioning
confidence: 99%